Determination of Fusarium Mycotoxin Beauvericin in Bombyx batryticatus by Liquid Chromatography-Tandem Mass Spectrometry (LC-MS/MS) - Jiang, X.; Chen, Y.J.; Shi, L.G. (Asian Journal of Chemistry, 2013)
Fusarium Mycotoxin beauvericin has been proven to be a potent antibiotic compound useful for bio-control and a potential antifungal and anticancer agent for human. The aim of this study was to determine the level of Fusarium mycotoxin beauvericin in Bombyx batryticatus using LC-MS/MS and observe its content changes in production process within 12 days. The method yielded satisfactory precision, stability and repeatability (RSD: 0.63 %, 0.96 %, 1.16 %). Average recovery of three spiked levels was 100.3 % with RSD 4.54 %. The level of beauvericin changes with a certain law in dead silkworm bodies. Fusarium mycotoxin beauvericin content was almost zero in the first four days, then extended increasing and reached its maximum in 10th day, which was high up to 43.08 μg/g. The trend of Fusarium mycotoxin beauvericin level declined from 10th day. This is the first study to report the content of Fusarium mycotoxin beauvericin in B. batryticatus.